The role of public money in the digital age by - Francisco Rivadeneyra; Scott Hendry; Alejandro García (Bank of Canada, 2024)
A well-functioning monetary system is characterized by public and private forms of money that exchange at par as value flows freely between them. This is essential for efficient transacting and contracting in a market economy. A relevant retail public money - whether in the form of cash, a central bank digital currency or both - is a necessary component of such a monetary system. Some of the other necessary components include financial regulation, deposit insurance, a monetary policy framework and lender of last resort facilities. A monetary system without retail public money would be prone to fragmentation, where different types of private money do not trade at par, and to market failures arising from the network effects of payment platforms
Keywords: E42; E50; E58; 330; Central bank research; Digital currencies and fintech; Payment clearing and settlement systems